2017
DOI: 10.1523/eneuro.0272-17.2017
|View full text |Cite
|
Sign up to set email alerts
|

The Progestin Receptor Interactome in the Female Mouse Hypothalamus: Interactions with Synaptic Proteins Are Isoform Specific and Ligand Dependent

Abstract: Progestins bind to the progestin receptor (PR) isoforms, PR-A and PR-B, in brain to influence development, female reproduction, anxiety, and stress. Hormone-activated PRs associate with multiple proteins to form functional complexes. In the present study, proteins from female mouse hypothalamus that associate with PR were isolated using affinity pull-down assays with glutathione S-transferase–tagged mouse PR-A and PR-B. Using complementary proteomics approaches, reverse phase protein array (RPPA) and mass spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(50 citation statements)
references
References 133 publications
10
40
0
Order By: Relevance
“…Extending our earlier findings that showed that synaptic proteins interacted with ligand-activated PR, 16 in the present study, we identified a large number of synaptic proteins that interacted with PR-A in a ligand-independent but DA-dependent manner ( Table 2).…”
Section: Synaptic Proteins From Skf-treated Female Mouse Hypothalamsupporting
confidence: 86%
See 3 more Smart Citations
“…Extending our earlier findings that showed that synaptic proteins interacted with ligand-activated PR, 16 in the present study, we identified a large number of synaptic proteins that interacted with PR-A in a ligand-independent but DA-dependent manner ( Table 2).…”
Section: Synaptic Proteins From Skf-treated Female Mouse Hypothalamsupporting
confidence: 86%
“…The recombinant proteins containing full-length mouse PR-A or PR-B fused to a GST tag were expressed in Spodoptera frugiperda (Sf9; RRID:CVCL_0549) insect cells at the Baculovirus/Monoclonal Antibody Facility of the Baylor College of Medicine as described previously. 16,58 Insect cell cultures for GST-PR-A or GST-PR-B were grown in the absence of PR ligand. The Sf9 cell pellets containing PR were homogenised in buffer containing 10 mmol L -1 Tris, 10%…”
Section: Glutathione S-transferase (Gst)-tagged Mouse Prsmentioning
confidence: 99%
See 2 more Smart Citations
“…In animal research, there is strong evidence for estrogen-dependent synaptic remodeling in the hippocampus (Woolley and McEwen 1993;Yankova et al 2001;Qiu et al 2013) and prefrontal cortex (Khan et al 2013). Likewise, progesterone has also been shown to increase dendritic spine number and density in cortical neuron cultures (Sanchez et al 2013;Acharya et al 2017). Although this suggests similar mechanism of action for both sex hormones, animal data strongly indicate that the effects are context dependent and progesterone might facilitate some of these estrogenic actions, while modulating or opposing others (McEwen and Milner 2017).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%